Growth, survival rate and fatty acid composition of sterlet (Acipenser ruthenus) larvae fed fatty acid‐enriched Artemia nauplii. (3rd August 2018) - Lundova, Katsiaryna; Kouril, Jan; Sampels, Sabine; Matousek, Jan; Stejskal, Vlastimil
Abstract: We evaluated the growth and survival rate of sterlet ( Acipenser ruthenus) larvae fed Artemia nauplii enriched with Olioω3 or Red Pepper commercial emulsions (BernAqua NV, Belgium). Sterlet larvae, 0.022 ± 0.002 g body weight, were randomly assigned to one of three feeding regimes with two different feeding durations. After administering live feed for 7 or 14 days, larvae were weaned onto commercial food and reared to 36 days posthatching (28 days of feeding). There were no significant differences in body weight among groups at the end of the trial. A significantly higher survival rate ( p < 0.05) was observed in larvae fed Artemia enriched with Red Pepper for 14 days compared to other feeding regimes. Based on the analysis of growth parameters, we can conclude that 7 days of live feeding to be sufficient for efficient rearing of sterlet larvae. And longer duration of live feeding with use of special enrichment can be recommended for a higher survival rate.